Influence of carbonation on the bound chloride concentration in different cementitious systems. (4th October 2021) - Zheng, Yujia; Russell, Mark; Davis, Geoff; McPolin, Daniel; Yang, Kai; Basheer, P.A.M.; Nanukuttan, Sreejith
Graphical abstract: Highlights: Hinderance effect – newly formed carbonates immobilise free and bound chlorides. Carbonates envelope minerals that contain physically/chemically bound chlorides. Hinderance effect dominant in low water binder ratio mixes. Positive linear relationship between pH and bound chlorides. Boundchlorides, C bind = 2.538 × p H - 19.565 . Abstract: Deterioration of reinforced concrete is often studied in idealised scenarios where only one exposure environment is dominant. For example, to study concrete structures exposed to de-icing salt environments, the effect of a cyclic wetting and drying regime is considered, but deterioration by carbonation is not given any emphasis. However, some studies have shown that carbonation could result in the release of bound chlorides and this could lead to an increase in chloride content near steel in reinforced concrete. Through an investigation on the influence of carbonation on the bound chlorides in different cementitious pastes, this paper highlights the positive initial effects that carbonation has on the chloride binding behaviour and later the changes that occur in both the pH of concrete and the bound chloride content for both low and high w/b mixes. Two mathematical expressions are put forward for mapping: (i) the changes in apparent pH as a function of the duration of carbonation and mix ingredients; and (ii) the reduction in the bound chlorides with a proportional reduction in apparent pH. The latter is valuable in quantifying the changes to binding capacity in service life models due to carbonation, with the help of a simple pH measurement.